Mommy brain : discover the amazing power of the maternal brain - Pawluski, Jodi (Demeter Press, 2023)
"Do you sometimes have the feeling that your brain is going to mush and that your baby is literally sucking the life out of your neurons? Don't worry, you're not losing your mind! In fact, your brain is getting a complete makeover and focusing on new areas of learning which are essential for parenting. In this book, Dr Jodi Pawluski questions our relationship with motherhood and explores, in an unprecedented way, the fantastic universe of the maternal, and parental, brain. Drawing on numerous scientific studies, including her own neuroscience research and experience, she provides insight into how your brain really changes with motherhood, and why."--